KAUM AWAM SEBAGAI “GARAM DAN TERANG DUNIA” DI ZAMAN TEKNOLOGI DIGITAL - Ireneus Sibori; Antonius Denny Firmanto; Nanik Wijiyati Aluwesia (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2022)
The Industrial Revolution 4.0 changed the work system, mindset and face of the world. In an era that is no longer the same, digital technology is growing rapidly. This change presents a new challenge for the Catholic Church in its existence in the midst of the world. The Church recognizes this change and seeks to use technological advances as a means of proclaiming God's love. In this case, the Church tries to invite Catholic laity to rise up and answer the call of Christ. The laity are the ones who are called. Since receiving baptism they have all been called to be salt and light to their fellowmen. Yet the laity often mistake that they have the lower dignity of the priests and are not worthy to be preachers of Christ. The Catholic Church tries to make people realize that they have the same dignity as children of God. They are also called people. They are a mirror image of the face of Christ in the midst of the world. Their presence in direct contact with the world is the hope that the love of Christ will be felt by all nations. In this era of industrial revolution 4.0, common people are expected to become salt and light for others. The methodology I use in this paper is data collection by means of questionnaires and literature study of various books and articles related to the title of this research. The findings in this paper are that Catholic laypeople are still less aware of their role as salt and light especially in the era of the 4.0 industrial revolution. Therefore the Catholic Church must do more to raise up the laity in answering the call of Jesus Christ as the salt and light of the world.